P‐215: Definition and Design of a Good Light. Issue 1 (2nd June 2017) - Jou, Jwo-Huei; Singh, Meenu; He, Zhe-Kai; Su, Yu-Ting
Abstract : Only energy‐saving can no longer be justified as a good light. It should also be healthy with high light‐quality. We have hence developed a new approach toward designing good lights for both display and lighting technologies, depending on the required color temperature.